2013
DOI: 10.1186/1471-2407-13-322
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine (C-X-C) ligand 1 (CXCL1) protein expression is increased in aggressive bladder cancers

Abstract: BackgroundChemokines, including chemokine (C-X-C motif) ligand 1 (CXCL1), may regulate tumor epithelial-stromal interactions that facilitate tumor growth and invasion. Studies have linked CXCL1 expression to gastric, colon and skin cancers, but limited studies to date have described CXCL1 protein expression in human bladder cancer (BCa).MethodsCXCL1 protein expression was examined in 152 bladder tissue specimens (142 BCa) by immunohistochemical staining. The expression of CXCL1 was scored by assigning a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 30 publications
3
59
0
Order By: Relevance
“…The IHC staining pattern revealed that GROα protein was localized in the cytoplasm of cancer cells. It has been previously reported that positive GROα staining is diffuse and not associated with any specific cell types [28]. The reason for the different localization of GROα might be because of the use of dissimilar antibodies as well as differences in the samples collected.…”
Section: Discussionmentioning
confidence: 99%
“…The IHC staining pattern revealed that GROα protein was localized in the cytoplasm of cancer cells. It has been previously reported that positive GROα staining is diffuse and not associated with any specific cell types [28]. The reason for the different localization of GROα might be because of the use of dissimilar antibodies as well as differences in the samples collected.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the HPV-positive patients had shorter OS and PFS compared with the HPV-negative patients, but only the levels of HGF, FIGO stage and pelvic lymph node metastasis were independent prognostic factors in the multivariate Cox analysis. Cheng et al (42) reported that GRO-1 may be a promising adverse prognostic molecular marker, and Miyake et al (43) confirmed the poor prognostic value of GRO-1 in bladder cancer. Numerous studies have demonstrated the prognostic value of sE-selectin in colorectal cancer (31,34).…”
Section: ------------------------------------------------------------mentioning
confidence: 97%
“…[14][15][16][17] Chemokines are critical to the inflammatory response of humans and are secreted to recruit cells from the immune system in response to viral infection and allergic disorders. 18 Some chemokines are even suggested to be involved in modulating the migration of normal cells. Scientists have recently discovered that the deactivation of chemokines may implicate the initiation or progression of a variety of tumors.…”
Section: Introductionmentioning
confidence: 99%